Combined Surgical Approach for Safe and Effective Rejuvenation of the Lower Eyelids - Yordanov Y. P. (Acta Medica Bulgarica)
Blepharoplasty is among the most demanded plastic surgery procedures worldwide. The popularity of the eyelid surgical rejuvenation is closely related to the remarkable improvement in facial aesthetics that these procedures bring to the patients with relatively short recovery period. However, these surgical interventions are among the most challenging since form, function and aesthetics have to be equally considered, preserved and improved. This is particularly true when dealing with age-related changes of the lower eyelids.